Pengaruh Promosi Penjualan dan Motivasi Belanja Hedonik Terhadap Impulse Buying di Era Pandemi - Endar Sulistyowati; Destina Paningrum; Anggit Dyah Kusumastuti (Jurakunman (Jurnal Akuntansi dan Manajemen), 2022)
The impact of the Covid-19 pandemic on the community in Giriwoyo Subdistrict, Giriwoyo District,Wonogiri Regency has created a new habit of shopping online and causes impulse buying behaviour. Sales promotion and hedonic shopping motivation are significant factors in increasing impulse buying. Therefore, this study aims to determine the effect of sales promotions consisting of discounts, cashback, vouchers, events, and hedonic shopping motivations consisting of adventure shopping, gratification shopping, role shopping, social shopping, ide shoppong, and value shopping, on impilse buying variables during the pandemic era for Tokopedia application users in Giriwoyo subdistrict, Giriwoyo District, Wonogiri. This research is decriptive research with a quantitative approach. The population was the entire community in the Giriwoyo subdistrict, Giriwoyo District, Wonogiri. The sampling technique usedthe purposive sampling technique, and the number of research samples was 160 respondents. The results show that the sales promotion variable and hedonic shopping motivation influenced the impulse buying variable in the pandemic era for users of Tokopedia application in Giriwoyo subdistrict, Giriwoyo District, Wonogiri. It can be seen from the Adjusted R Square value of 0.751. It means that the independent variable in explaining the dependentvariable is 75.1%, other variables explain the 24.9% out of this study.Keywords : Hedonic Shopping Motivation; Impulse Buying;Sales Promotion